2013
DOI: 10.5688/ajpe77232
|View full text |Cite
|
Sign up to set email alerts
|

A Prescription Analysis Exercise in a Pharmaceutical Care Laboratory Course

Abstract: Objective. To assess the impact of a new prescription analysis exercise in a second-year pharmaceutical care laboratory course. Design. A new prescription analysis exercise was created and implemented that shifted the focus from strictly identifying errors and omissions to identifying and correcting them. Students used electronic label templates and mock prescription materials to correct various errors and omissions commonly seen in practice. Assessment. Forty-one percent of students received full credit for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…11 Initial studies in the area of prescription review in pharmacy school curricula demonstrated that with the use of activelearning techniques such as role playing and simulations, students perform better when required to identify and correct the prescription error rather than identifying the error alone. 12,13 Furthermore, students' awareness of their role in preventing medication errors increased as a result of taking the medication safety laboratory sessions. 13 Computer-based modules 2,3,14 and "mock pharmacy" 12 techniques have also been identified as modes to further enhance active learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Initial studies in the area of prescription review in pharmacy school curricula demonstrated that with the use of activelearning techniques such as role playing and simulations, students perform better when required to identify and correct the prescription error rather than identifying the error alone. 12,13 Furthermore, students' awareness of their role in preventing medication errors increased as a result of taking the medication safety laboratory sessions. 13 Computer-based modules 2,3,14 and "mock pharmacy" 12 techniques have also been identified as modes to further enhance active learning.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Furthermore, students' awareness of their role in preventing medication errors increased as a result of taking the medication safety laboratory sessions. 13 Computer-based modules 2,3,14 and "mock pharmacy" 12 techniques have also been identified as modes to further enhance active learning.…”
Section: Introductionmentioning
confidence: 99%
“… Limberger (2013) [ 27 ] Franciscan University Center (UNIFRA)/the seventh semester of pharmacy Identifying the medicines of choice; identifying and solving drug-related problems Case study Not available Lucas et al (2013) [ 28 ] University of Charleston School of Pharmacy, Charleston, West Virginia/second year and third year of a doctor of pharmacy (PharmD) program Pharmacotherapy: ” develop strategies to increase patient understanding, motivation, and adherence to treatment plans; identify and prevent drug-related problems; effectively monitor, assess, and optimize therapeutic plans; and apply current practice guidelines to therapeutic recommendations” Discussion – based activities, e.g. patient cases Subjective increase in the students' sense of responsibility and capability for the self-learning process Norose (2013) [ 29 ] Hokkaido Pharmaceutical University School of Pharmacy, Otaru, Hokkaido, Japan/fifth year of pharmacy Creating care plan for patients according to SOAP – plan: Subjective information, Objective information, Assessment, and Plan Problem – based learning using SP (standardized patients) method Students' comments: the experience helped to understand how to create a care plan and the importance of interview with the patient in that process Suno et al (2013) [ 30 ] Medical Education Center, Okayama University/undergraduates pharmaceutical care practices Team – based learning 87.3 ± 9.3% students were satisfied with TBL method; individual readiness assessment test (IRAT) score before the TBL sessions were lower than the group readiness assessment test (GRAT) score during TBL Waitzman & Dinkins (2013) [ 31 ] UNC Eshelman School of Pharmacy, University of North Carolina, Chapel Hill, North Carolina/second-year pharmacy students prescription analysis exercise – identification of errors and omissions, followed by their correction Hands-on exercises with index card box with stock bottle cards, prescriptions and labeled medicine bottles 94% of students found the new method of teaching prescription validation more realistic and practical than the one used in previous semesters Mesquita et al (2015) [ 32 ] Department of Pharmacy, Federal University of Ser...…”
Section: Resultsmentioning
confidence: 99%
“… PC aspect Authors Pharmaceutical care for a patient suffering from a specific disease (e.g. diabetes) Benedict & Schonder (2011) [ 22 ] Campbell et al (2012) [ 24 ] Sterrett et al (2012) [ 25 ] Katoue & Al Haqan (2013) [ 26 ] Martinez et al (2017) [ 34 ] Marvanova & Henkel (2018) [ 36 ] Dispensing the prescription in the context of correctness, verification of medical recommendations and detection of drug problems Limberger (2013) [ 27 ] Lucas et al (2013) [ 28 ] Waitzman & Dinkins (2013) [ 31 ] Gossenheimer et al (2017) [ 33 ] Nasser et al (2021) [ 39 ] Patient education (pharmacist as an educator) Lucas et al (2013) [ 28 ] Foppa et al (2021) [ 38 ] Nasser et al (2021) [ 39 ] Faustino et al (2022) [ 40 ] Patients' medicines related needs Mesquita et al (2015) [ 32 ] Faustino et al (2022) [ 40 ] Develop a pharmaceutical care plan Woelfel et al (2011) [ 23 ] Norose (2013) [ 29 ] Geriatric care Woelfel et al (2011) [ 23 ] Cultural competency Prescott & Nobel (2019) [ 37 ] …”
Section: Resultsmentioning
confidence: 99%
“…Many faculty members took advantage of the introductions of skills laboratories to address key educational outcomes as part of their courses [2][3][4][5][6] and to improve required skills. At Creighton University, the pharmacy skills laboratory (PSL) course sequence was implemented in 2009.…”
Section: Introductionmentioning
confidence: 99%